Results and Pitfalls in Prenatal Cytogenetic Diagnosis - Hsu, Lillian Y. F. (1973)
Since 1969, we have cultured over 200 diagnostic amniotic fluids. Of these, 183 were for cytogenetic diagnosis. The chromosome analysis was successful in 168 cases. The indications and the results of the affected fetuses (followed by therapeutic abortion) are: (1) previous child with Down's syndrome: 62 cases (1:47,XX,+21); (2) advanced maternal age: 54 cases (1:47,XXY; 1:45,X/46,XY mosaicism; 1:47,+18); (3) previous child with multiple anomalies: 12 cases; (4) previous child with 47,XY,+18 or 47,+13: five cases; (5) translocation carrier: two cases; (6) parental mosaicism: three cases; (7) X-linked disorders: six cases (3:XY); (8) others: 24 cases. We have found firstly, that for prenatal sex determination, karyotype analysis of the cultured amniotic fluid cells is the only accurate means and that caution must be taken if sex chromatin and Y-fluorescent body determination from the uncultured amniotic fluid cells is used. Secondly, that diagnosis of chromosomal mosaicism can be problematic as exemplified by our case of 45,X/46,XY mosaicism, where only 45,X cells were recovered from the first culture. Thirdly, that in cases with enlarged satellites, cells of late prophase or early metaphase must be used to eliminate confusion with translocations. We encountered three cases of enlarged satellites—one in the D group and two in the G group—and all three resulted in normal infants. Fourthly, that the karyotype may be altered by contamination and/or treatment or other unknown factors. We have observed two such cases where each mother delivered a normal infant.